(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article examines the formation of kinship terms in the Khorezm dialect of the Uzbek language and in the English language based on linguistic analysis. Kinship terminology in both language systems is compared through historical layers, external influences, morphological word-formation methods, and social factors. In particular, the influence of ancient Turkic, Persian, Arabic, and Russian languages on the Khorezm dialect is analyzed, as well as the role of gender and age distinctions in kinship terms. In English, the linguistic features of kinship terms formed on the basis of Germanic roots, as well as Latin and French language layers, are revealed.